There and Back Again—The Journey of LiNiO2 as a Cathode Active Material. Issue 31 (2nd May 2019) - Bianchini, Matteo; Roca‐Ayats, Maria; Hartmann, Pascal; Brezesinski, Torsten; Janek, Jürgen
Abstract: This Review provides a comprehensive overview of LiNiO2 (LNO), almost 30 years after its introduction as a cathode active material. We aim to highlight the physicochemical peculiarities that make LNO a complex material in every aspect. We specifically stress the effect of the Li off‐stoichiometry (Li1−z Ni1+z O2 ) on every property of LNO, especially the electrochemical ones. The key instability issues that plague the compound and the strategies that have been implemented so far to overcome them are discussed in detail. Finally, the open questions that remain to be addressed by the scientific community are summarized, and the research directions that seem the most promising to enable LNO to be fully exploited are elucidated. Abstract : Taking charge : LiNiO2 is one of the most heavily investigated layered oxides for use as the cathode active material of Li‐ion batteries. This Review gives a comprehensive overview of this compound, almost 30 years after its introduction. The focus lies in the effect of Li off‐stoichiometry, the key instability issues that plague the material and the strategies to overcome them, the open questions, and the most promising future research directions.